The Effect of Regional Income (PAD), Balancing Funds, and Total Population Againts Local Government Expenditure In West Java 2016-2018 Period - Rifki Yudha Aditama; Eni Setyowati (Universitas Muhammadiyah Makassar, 2022)
This study focuses on the elements that affect local government spending with several independent variables, including inflation of local revenue, balancing funds, and population. This study relies secondary data from twenty-seven regencies/cities in West Java Province from 1996 to 2020, as well as panel data regression using Pooled Least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (REM) as analytic techniques. The Chow and Hausman tests are used in the estimate measures. According to the study's findings, the Regional Original Revenue, Balancing Fund has a negative and substantial influence on Regional Government Expenditures in West Java Province, however population has no significant effect on Regional Government Expenditures in West Java